2020
DOI: 10.1177/0004563220931876
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different analytical platforms and methods on the performance of population-specific adjusted calcium equation

Abstract: Background A recent attempt to improve the diagnostic value of adjusted calcium addressed a primary care-specific adjusted calcium equation, but validated the new equation for Roche Cobas, BCG and NM-BAPTA methods only. In this study, we aim to validate a population-specific equation for other methods and platforms. Method We collected retrospective patient data-sets from 15 hospital laboratories using a range of commercially available analytical platforms and methods for calcium and albumin measurements. Raw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…However, our data from 15 clinical laboratories show significantly lower means, with an inpatient population mean for calcium of 2.2 mmol/L and a primary care calcium population mean of 2.3 mmol/L. 2 We also showed that the calcium population mean has a major impact on the outcome of the adjusted calcium equation. 2 When the normalized equation performance was tested against ionized calcium in 123 subjects, as described in our population-specific equation paper, 3 the normalized equation overestimated calcium status in healthy individuals and failed to identify any of the nine hypocalcaemic subjects.…”
Section: In Reply To Robertsmentioning
confidence: 54%
See 1 more Smart Citation
“…However, our data from 15 clinical laboratories show significantly lower means, with an inpatient population mean for calcium of 2.2 mmol/L and a primary care calcium population mean of 2.3 mmol/L. 2 We also showed that the calcium population mean has a major impact on the outcome of the adjusted calcium equation. 2 When the normalized equation performance was tested against ionized calcium in 123 subjects, as described in our population-specific equation paper, 3 the normalized equation overestimated calcium status in healthy individuals and failed to identify any of the nine hypocalcaemic subjects.…”
Section: In Reply To Robertsmentioning
confidence: 54%
“…2 We also showed that the calcium population mean has a major impact on the outcome of the adjusted calcium equation. 2 When the normalized equation performance was tested against ionized calcium in 123 subjects, as described in our population-specific equation paper, 3 the normalized equation overestimated calcium status in healthy individuals and failed to identify any of the nine hypocalcaemic subjects. The same finding was observed when the normalized equations for 15 hospitals were compared with inpatient equations derived using Payne's criteria (Figure 1).…”
Section: In Reply To Robertsmentioning
confidence: 61%
“…This issue of the Annals sees the publication of two papers by Jassam et al. 1 , 2 which, together with their two previously published papers, 3 , 4 make a short series on the broad theme of calcium albumin adjustment equations.…”
mentioning
confidence: 99%
“…I read with interest the recent papers by Jassam et al., 1 , 2 regarding the use of population-specific adjusted calcium equations. In particular, the factors which may affect the performance of locally derived adjustment equations are investigated in more detail revealing many potential pitfalls.…”
mentioning
confidence: 99%